Methodology for Validity and Reliability Testing of a New Questionnaire Used in Medical Research: Course Content for Research Methodology Subject. - Sahu, Seema Gupta (Homoeopathic Heritage, 2023)
It is important for researchers to choose a correct and relevant research tool, to obtain a result, that has internal as well as external validity. Validity and reliability, which measure how accurate and consistent is the research tool (primarily questionnaires), have been shown in different studies; but researchers normally overlook them before using a particular primary questionnaire. This has been connected to the lack of understanding of these tests. In medical science, impact of a chronic disease on health and/or the effects of medical intervention is measured through Health-related quality of life (HRQoL). Here, an attempt is made so that researchers try to choose the right research instrument by reading review articles that peek into and discuss the reliability and validity of a research instrument (questionnaires in particular). This article delineates the various types of tests regarding reliability and validity.